2018 IEEE Applied Power Electronics Conference and Exposition (APEC) 2018
DOI: 10.1109/apec.2018.8341250
|View full text |Cite
|
Sign up to set email alerts
|

Increasing emitter efficiency in 3.3-kV enhanced trench IGBTs for higher short-circuit capability

Abstract: Abstract-In this paper, a 3.3-kV Enhanced Trench IGBT has been designed with a high emitter efficiency, for improving its short-circuit robustness. The carrier distribution profile has been shaped in a way that it is possible to increase the electric field at the surface of the IGBT, and thereby, counteract the Kirk Effect onset. This design approach is beneficial for mitigating high-frequency oscillations, typically observed in IGBTs under short-circuit conditions. The effectiveness of the proposed design rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Effect of collector doping concentration charge-field interactions can be counteracted by increasing the electric field at the emitter of the IGBT, in this way, the electric field becomes strong and not influenced by the excess of carriers in this region. One option to achieve a stronger electric field is to increase the hole injection, for example, by increasing the bipolar current gain α pnp [15]. This can be done by selecting a higher doping concentration of the p + collector layer.…”
Section: Effect Of High Biolar Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of collector doping concentration charge-field interactions can be counteracted by increasing the electric field at the emitter of the IGBT, in this way, the electric field becomes strong and not influenced by the excess of carriers in this region. One option to achieve a stronger electric field is to increase the hole injection, for example, by increasing the bipolar current gain α pnp [15]. This can be done by selecting a higher doping concentration of the p + collector layer.…”
Section: Effect Of High Biolar Gainmentioning
confidence: 99%
“…The aim is to increase the electric field at the IGBT's surface and counteract the weak electric field. A sensitivity study has been performed in [6], [11], [15] and later in [10], varying different parameters and investigating its influence on the short-circuit oscillation behavior. Those studies have proven that the IGBT oscillations are more likely to be observed when the device is operated at low DC-link voltages, high positive gate voltages and low case temperatures, because the electric field becomes weaker at the emitter.…”
Section: Introductionmentioning
confidence: 99%